Compensated non‐linear root water uptake model and identification of soil hydraulic and root water uptake parameters - Sonkar, Ickkshaanshu; Sudesan, Soorya; Suryanarayana Rao Kotnoor, Hari Prasad (Irrigation and drainage, 2022)
The improvement in soil and root parameterization is a key to enhance the root zone moisture depletion pattern prediction capability. In the present study, a new compensated non‐linear root water uptake (RWU) model is developed to analyse moisture flow under various crop growth and soil conditions. This is achieved by introducing a water stress index in the calibrated non‐linear RWU model that takes care of RWU compensation. The present study also deals with the identifiability of soil hydraulic and RWU parameters using soil moisture and percolation data with an inverse approach. For parameter estimation, the numerical model has been coupled with a genetic algorithm‐based optimizer. The efficacy of the coupled simulation‐optimization model is tested for wheat (Triticum aestivum) crops grown in loamy, sandy clay loam, and sandy loam soil. The study shows that the RWU is less sensitive to soil moisture dynamics in sandy loam soil due to predominant vertical flow. Further, these parameters were estimated for four major Indian crops, that is, berseem (Trifolium alexandrinum), wheat, maize (Zea mays), and pearl millet (Pennisetum glaucum). In soils of higher hydraulic conductivity, the inverse approach was found to be ill‐posed in estimating RWU and soil parameters using only soil moisture information. Hence, for such soils, both soil moisture and percolation data are necessary for estimating these parameters uniquely. Résumé L'amélioration de la paramétrisation du sol et des racines est essentielle pour améliorer la capacité de prédiction du modèle d'épuisement de l'humidité de la zone racinaire. Dans la présente étude, un nouveau modèle d'absorption d'eau racinaire non linéaire compensé (RWU) est développé pour analyser le flux d'humidité dans diverses conditions de croissance des cultures et de sol. Ceci est réalisé en introduisant un indice de stress hydrique dans le modèle calibré non linéaire d'absorption d'eau par les racines qui prend en charge la compensation de l'absorption d'eau par les racines. La présente étude traite également de l'identifiabilité des paramètres hydrauliques du sol et de la RWU en utilisant les données d'humidité du sol et de percolation profonde avec une approche inverse. Pour l'estimation des paramètres, le modèle numérique a été couplé à un optimiseur basé sur un algorithme génétique. L'efficacité du modèle couplé de simulation‐optimisation est testée pour les cultures de blé (Triticum aestivum) cultivées dans des sols limoneux, argilo‐sableux et limoneux sableux. L'étude montre que la RWU est moins sensible à la dynamique de l'humidité du sol dans les loams sableux en raison de l'écoulement vertical prédominant. En outre, ces paramètres ont été estimés pour quatre grandes cultures indiennes, à savoir le bersim (Trifolium alexandrinum), le blé, le maïs (Zea mays) et le mil (Pennisetum glaucum). Dans les sols de conductivité hydraulique plus élevée, l'approche inverse s'est avérée mal posée dans l'estimation de la RWU et des paramètres du sol en utilisant uniquement les informations sur l'humidité du sol. Par conséquent, pour de tels sols, les données d'humidité du sol et de percolation profonde sont nécessaires pour estimer ces paramètres de manière unique.